(untitled) (Research, Society and Development, 2022)
The term humanization has been gaining prominence in the health area, especially in nursing, because it is the one who spends most of the time providing care to the patient. Knowing the importance of providing humanized care, one perceives the need to show how nurses mean humanization, and what behaviors they apply in their daily lives. The aim of this study is to understand how humanized conducts in nursing care can contribute to patient improvement, in the perception of nurses from two hospitals in the interior of the state of Rio Grande do Sul. This is a descriptive qualitative research, in which seven nurses working in hospitals in two small municipalities through an instrument elaborated by the researcher. The main results show that nurses know and signify the term humanization, according to their daily experiences and perceptions, in addition to employing conducts that they consider humanized in everyday life. They point out as hindering factors work overload, low pay, excessive demand, and lack of professionals, believe that humanized care can contribute to the improvement of the patient. We conclude that the professionals were satisfied with the work that has been carried out by them, but that improvements could still be made, for the factors pointed out as hindering factors, it is also important to maintain and provide opportunities, permanent and constant education in opening spaces for a discussion about what is already done, and what can be improved, for the proper functioning of services.